SEMA’AN OF THE QUR’AN REBO WEKASAN IN JAVA: A STUDY OF THE LIVING QUR’AN - Ikhwanuddin, Mohammad; Ali, Moh.; Khumairoh, Elly; Lathifah, Ummul; Ramadhani, Shinta Salwa (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2022)
The Rebo Wekasan celebration for the Indonesian Muslim community begins with information from parents from generation to generation, teachers to students, and elders to younger generations without mentioning a special event. This culture continues to be sustainable, especially in Javanese society, and Wonoayu Sidoajo is no exception in East Java. This celebration is carried out because of deep concern from the belief that Allah has sent down 320,000 disasters on the last Wednesday of the month of S}afar in the Hijri year, called Rebo Wekasan. The ancient Jahiliyah community, including the Arabs, often said the month of S}afar was the month of Tasa'um or bad luck. Some Muslims still believe this assumption today, including some Indonesians, especially the Javanese people. Based on this phenomenon, how can this tradition be preserved and commemorated, especially in Wonoayu? This question is the focus of attention in this research. This research is a living Qur’an study using a phenomenological and library research approach based on social phenomena in Wonoayu District, Sidoarjo. The results of this study indicate that in the Rebo Wekasan tradition, there is a living Qur’an phenomenon in the form of a practice carried out by carrying out the Sema’an of the Qur’an and reading surah Yasin 3 times with the hope that because of the blessings the community is safe from all kinds of diseases.